Carboxylato‐ and squarato‐bridged dinuclear/tetranuclear Cu(II) complexes: Synthesis, magnetic property, and protein binding studies. (18th September 2022) - Patra, Apu; Carrella, Luca M.; Saren, Dama; Mahish, Manas Kumar; Zangrando, Ennio; Puschmann, Horst; Rentschler, Eva; Manna, Subal Chandra
Abstract : Two new Cu(II) complexes [Cu2 (L)2 (mb)](ClO4 )·0.5H2 O (1 ) and [Cu4 (L)4 (sq)(H2 O)2 ](ClO4 )2 ·2H2 O (2 ) (HL = 2‐[(2‐morpholine‐4‐yl‐ethylimino)‐methyl]‐phenol); mb = 4‐methyl benzoate; sq 2− = C4 O4 2− squarate dianion) have been synthesized and characterized by single crystal X‐ray analysis, electrospray ionization mass spectrometry, and infrared spectroscopic technique. The structural determination showed the Schiff base acting as tridentate ligand coordinating the copper(II) atoms by the phenoxo, imino and morpholine nitrogen donors to give comparable Cu(L) entities in both complexes 1 and 2 . Complex 1 is a dinuclear cationic species built by a 4‐methylbenzoate anion coordinating two Cu(L) moieties. The two Cu(II) centers are chemically equivalent exhibiting a distorted square pyramidal geometry. Complex 2 is tetranuclear and it is formed by a centrosymmetric squarate core connected to four Cu(L) complex units to give a cationic complex counterbalanced by perchlorate anions. Of the two independent Cu(II) atoms, Cu1 exhibits a square pyramidal coordination sphere, whereas Cu2 is better described as square planar. The crystal packing of complex 2 shows a polymeric arrangement through H‐bonding. Magnetic measurements show antiferromagnetic coupling in both the complexes. The interaction of complexes with hen egg lysozyme has been investigated by using UV–vis absorption and 2D/3D fluorescence spectroscopic techniques and the calculated values of binding constants, Kbin, are (5.9 ± 0.11) × 10 4, (17.39 ± 0.04) × 10 4, and (10.1 ± 0.07) × 10 4 M −1 for HL, 1, and 2, respectively. Abstract : Two copper(II) complexes [Cu2 (L)2 (mb)](ClO4 )·0.5H2 O (1 ) and [Cu4 (L)4 (sq)(H2 O)2 ](ClO4 )2 ·2H2 O (2 ) (HL = 2‐[(2‐morpholine‐4‐yl‐ethylimino)‐methyl]‐phenol); mb = 4‐methyl benzoate; sq 2− = squarate dianion) have been synthesized and structurally characterized. Magnetic measurements show antiferromagnetic coupling in both the complexes. The interaction of the ligand and complexes with lysozyme, studied via UV–vis absorption and two‐/three‐dimensional fluorescence spectroscopic techniques, showed that the characteristic fluorescence of lysozyme is quenched through a static mechanism.